New rules of the game? Education and governmentality in Chinese migration to Poland. (September 2019) - Kardaszewicz, Krzysztof
The Chinese in Poland are an understudied but rapidly growing migrant community, undergoing a transition from an established pattern of economic chain migration to one based on investment of wealth in pursuit of a better life environment. Educational immigration by middle-class families provides insight into a broader trend of popular resistance to China's established model of governmentality. Refusing to conform to prescribed patterns of achievement and social mobility, these families exemplify a younger generation's aspirations and challenges involved in transnational mobility, which go beyond the traditional capital accumulation strategies.